Harnessing primary, secondary and tertiary genepools for durable wheat disease resistance - Anisa Blower; Rumiana V. Ray; Stephen Rawsthorne; Phil J. Howell; Fiona J. Leigh; Kostya Kanyuka (Theoretical and Applied Genetics, 2025)
Bread wheat ( Triticum aestivum ), a cornerstone of global food security contributing ~ 20% of daily caloric intake, faces increasing vulnerability to rapidly evolving pathogens. This is due in part to a narrowed genetic base following domestication and modern breeding. Wild and ancestral wheat relatives are critical reservoirs of disease resistance genes for breeding new, resilient varieties. This review explores the contributions of primary, secondary, and tertiary genepools of wheat to disease resistance, highlighting loci effective against fungal pathogens that threaten European wheat production. It examines the challenges of alien gene transfer including crossability barriers, hybrid necrosis, and suppressor loci and reviews modern breeding tools such as marker-assisted selection, genomic selection, and genome editing for harnessing exotic germplasm. By synthesising current knowledge, this review highlights the vital contribution of ancestral wheat germplasm in enhancing the resilience and productivity of future wheat crops against increasing biotic stresses.

An eight-founder wheat MAGIC population allows fine-mapping of flowering time loci and provides novel insights into the genetic control of flowering time - Laure Fourquet; Tobias Barber; Camila Campos-Mantello; Phil Howell; Beata Orman-Ligeza; Lawrence Percival-Alwyn; Gemma A. Rose; Hester Sheehan; Tally I. C. Wright; Friedrich Longin; Tobias Würschum; Dario Novoselovic; et al. (Theoretical and Applied Genetics, 2024)
Flowering time synchronizes reproductive development with favorable environmental conditions to optimize yield. Improved understanding of the genetic control of flowering will help optimize varietal adaptation to future agricultural systems under climate change. Here, we investigate the genetic basis of flowering time in winter wheat ( Triticum aestivum L.) using an eight-founder multi-parent advanced generation intercross (MAGIC) population. Flowering time data was collected from field trials across six growing seasons in the United Kingdom, followed by genetic analysis using a combination of linear modelling, simple interval mapping and composite interval mapping, using either single markers or founder haplotype probabilities. We detected 57 quantitative trait loci (QTL) across three growth stages linked to flowering time, of which 17 QTL were identified only when the major photoperiod response locus Ppd-D1 was included as a covariate. Of the 57 loci, ten were identified using all genetic mapping approaches and classified as ‘major’ QTL, including homoeologous loci on chromosomes 1B and 1D, and 4A and 4B. Additional Earliness per se flowering time QTL were identified, along with growth stage- and year-specific effects. Furthermore, six of the main-effect QTL were found to interact epistatically with Ppd-D1 . Finally, we exploited residual heterozygosity in the MAGIC recombinant inbred lines to Mendelize the Earliness per se QTL QFt.niab-5A.03 , which was confirmed to modulate flowering time by at least four days. This work provides detailed understanding of the genetic control of phenological variation within varieties relevant to the north-western European wheat genepool, aiding informed manipulation of flowering time in wheat breeding.

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

The effects of training population design on genomic prediction accuracy in wheat - Stefan McKinnon Edwards; Jaap B. Buntjer; Robert Jackson; Alison R. Bentley; Jacob Lage; Ed Byrne; Chris Burt; Peter Jack; Simon Berry; Edward Flatman; Bruno Poupard; Stephen Smith; et al. (Theoretical and Applied Genetics, 2019)

Applying association mapping and genomic selection to the dissection of key traits in elite European wheat - Alison R. Bentley; Marco Scutari; Nicolas Gosman; Sebastien Faure; Felicity Bedford; Phil Howell; James Cockram; Gemma A. Rose; Tobias Barber; Jose Irigoyen; Richard Horsnell; Claire Pumfrey; et al. (Theoretical and Applied Genetics, 2014)